Enhancing Elementary Students' Robotics Understanding and Learning Engagement via Creative Project-Based Activities at SDN Margorejo 1 Surabaya - Sidqon, Mochamad; Kridoyono, Agung; Yunanda, Anton Breva; Yuwono, Istantyo (Institut Teknologi Nasional, Bandung, 2025)
The perception of complexity and a lack of real-world relevance often hinder elementary school students' interest in robotics. This study aimed to evaluate the effectiveness of creative project-based learning in building a strong foundation in robotics and enhancing student engagement at SD Margorejo 1 Surabaya. By integrating design thinking principles and project-based learning, this approach sought to create authentic and meaningful learning experiences. Employing a qualitative case study methodology with a participatory action research design, fifth-grade students were involved in a series of robotics projects designed to address real-world problems in their local environment. Data were collected through participant observation, semi-structured interviews, and project artifact analysis. The findings revealed that creative project-based learning significantly increased students' interest in robotics. Students not only grasped fundamental robotics concepts but also developed critical thinking, creativity, and collaboration skills. Moreover, this approach effectively strengthened students' understanding of STEM (Science, Technology, Engineering, and Mathematics) concepts and fostered awareness of robotics' relevance in daily life. This study concludes that creative project-based learning is an effective strategy for building a strong robotics foundation and cultivating student interest at the elementary school level.